Patterns and Determinants of Judicial Reasoning in Deciding Women Economic Rights in Religious Courts - Yanti, Novi; Candra, Eki; Hafiz, Muhammad; Siregar, Indra Praja; Anggriani, Irien Violinda (Islamica: Jurnal Studi Keislaman, 2026)
This study examines judicial considerations regarding wife’s maintenance in marital cases based on an analysis of decisions of the Religious Court of Pekanbaru during the period 2019-2024. The objective of this research is to identify patterns of judicial reasoning in granting or denying wife’s maintenance, including normative foundations, the application of the concept of nushūz, the use of ex officio authority, the determination of maintenance amounts, and attention to the execution of court decisions. The main argument of this study asserts that decisions on wife’s maintenance are not uniform, but are shaped by a combination of legal and factual factors that form specific patterns of judicial consideration. This research employs a normative legal method with a case approach and content analysis of selected court decisions. The findings indicate a shift in judicial practice toward more substantive protection of wives’ rights, as reflected in the increasing use of ex officio authority and references to judicial policies. Nevertheless, disparities remain in the proof of nushūz, variations in maintenance amounts, and limitations in the effectiveness of decision enforcement. This study argues that the quality of protection for wife’s maintenance largely depends on the consistency of judicial reasoning and the design of operative rulings oriented toward enforceability.